An Assessment of Occupational Safety and Health Practices in Nepalese Garment Workers - Rai, Basanta (GS Spark: Journal of Applied Academic Discourse, 2023)
The article aims to assess the occupational safety and health (OSH) practices in Nepalese garment industries, particularly for home-based garment workers. The study uses a qualitative and descriptive methodology, including secondary information sourced from books, papers, published articles, and online platforms. The findings show a lack of scientific studies on OSH in the Nepalese garment sector and an unsatisfactory overall status of OSH in Nepal. The study finds poor occupational safety and health practices in the garment business, with insufficient safety precautions and workers who are unaware of hazards and preventive measures. Workers in this industry have a variety of health problems, including musculoskeletal illnesses, which are more common in the sewing department. Musculoskeletal problems are connected with factors such as age, gender, and educational status. The study emphasizes the importance of quick and comprehensive measures by the government, businesses, and employees to improve occupational safety and health in this industry. The article also emphasizes the complicated nature of garment manufacturing units.